Environmental Factors Affecting Microbiota Dynamics during Traditional Solid-state Fermentation of Chinese Daqu Starter - Li, Pan; Lin, Weifeng; Liu, Xiong; Wang, Xiaowen; Luo, Lixin (Frontiers in Microbiology, 2016)
In this study, we investigated the microbiota dynamics during two industrial-scale traditional solid-state fermentation (SSF) processes of Daqu starters. Similar evolution profiles of environmental parameters, enzymatic activities, microbial amounts and communities were observed during the medium temperature SSF (MTSSF) and low temperature SSF (LTSSF) processes. Orders of Rickettsiales and Streptophyta only dominated the initial two days, and Eurotiales only predominated from days 10 to 24, however, phylotypes of Enterobacteriales, Lactobacillales, Bacillales, Saccharomycetales and Mucorales both prevailed throughout the MTSSF and LTSSF processes. Nevertheless, the pH in MTSSF process on day 5 were 5.28, while in LTSSF process (4.87) significantly lower (P < 0.05). The glucoamylase activities in MTSSF process dropped from 902.71 to 394.33 mg glucose g-1 h-1 on days 5 to 24, while significantly lower (P < 0.05) in LTSSF process and decreased from 512.25 to 268.69 mg glucose g-1 h-1. The relative abundance of Enterobacteriales and Lactobacillales in MTSSF process constituted from 10.30% to 71.73% and 2.34% to 16.68%, while in LTSSF process ranged from 3.16% to 41.06% and 8.43% to 57.39%, respectively. The relative abundance of Eurotiales in MTSSF process on days 10 to 24 decreased from 36.10% to 28.63%, while obviously higher in LTSSF process and increased from 52.00% to 72.97%. Furthermore, lower bacterial richness but higher fungal richness were displayed, markedly differences in bacterial communities but highly similarities in fungal communities were exhibited, during MTSSF process comparatively to the LTSSF process. Canonical correspondence analysis revealed microbial structure transition happened at thermophilic stages under environmental stress of moisture, pH, acidity and pile temperature. These profound understanding might help to effectively control the traditional Daqu SSF process by adjusting relevant environmental parameters.